2017
DOI: 10.1111/gcbb.12481
|View full text |Cite
|
Sign up to set email alerts
|

Targeted subfield switchgrass integration could improve the farm economy, water quality, and bioenergy feedstock production

Abstract: Progress on reducing nutrient loss from annual croplands has been hampered by perceived conflicts between short-term profitability and long-term stewardship, but these may be overcome through strategic integration of perennial crops. Perennial biomass crops like switchgrass can mitigate nitrate-nitrogen (NO 3 -N) leaching, address bioenergy feedstock targets, and -as a lower-cost management alternative to annual crops (i.e., corn, soybeans) -may also improve farm profitability. We analyzed publicly available e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 48 publications
(79 reference statements)
1
49
0
Order By: Relevance
“…In a previous modeling study, Brandes et al. () showed that nitrate leaching could be reduced by 18% in Iowa if 12% of corn/soybean cropland was converted to switchgrass. Our analysis revealed that three counties in Iowa could reach this percentage of switchgrass cover, while simultaneously increasing total producer benefit by millions of dollars, when converting all corn/soybean cropland areas with breakeven switchgrass yields of up to 10.08 Mg ha −1 , assuming all land is owned and medium switchgrass price (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous modeling study, Brandes et al. () showed that nitrate leaching could be reduced by 18% in Iowa if 12% of corn/soybean cropland was converted to switchgrass. Our analysis revealed that three counties in Iowa could reach this percentage of switchgrass cover, while simultaneously increasing total producer benefit by millions of dollars, when converting all corn/soybean cropland areas with breakeven switchgrass yields of up to 10.08 Mg ha −1 , assuming all land is owned and medium switchgrass price (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For example, policymakers could set a target AC adoption rate and then use the high‐resolution analysis to identify the ideal land to meet this goal (Brandes et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…identifies environmentally sensitive areas (SooHoo et al 2017, Brandes et al 2018 or the current extent of existing agroforestry practices (Herder et al 2017) could further hone the identification of target regions for MSR alternatives.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations